2016
DOI: 10.1093/femsec/fiw220
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of anaerobic degraders of BTEX hydrocarbons in aquifers

Abstract: The degradation of benzene, toluene, ethylbenzene and xylene (BTEX) contaminants in groundwater relies largely on anaerobic processes. While the physiology and biochemistry of selected relevant microbes have been intensively studied, research has now started to take the generated knowledge back to the field, in order to trace the populations truly responsible for the anaerobic degradation of BTEX hydrocarbons in situ and to unravel their ecology in contaminated aquifers. Here, recent advances in our knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 119 publications
(196 reference statements)
1
61
0
3
Order By: Relevance
“…We can hypothesise that close to the reservoir of natural gas, dissolved hydrocarbons (i.e., short-chain alkanes, BTEX) may serve as exogenous nutrients and could be key factor shaping the composition of the communities. The literature on the topic is full of examples of the capacity of deltaproteobacteria and Firmicutes to grow on these organic molecules (Meckenstock et al, 2016;Lueders, 2017). Microbial communities populating subsurface environments have demonstrated such capacity for the biodegradation of hydrocarbons in the laboratory and in situ.…”
Section: Diversity Of Sulfate-reducing and Methanogenic Metacommunitiesmentioning
confidence: 99%
“…We can hypothesise that close to the reservoir of natural gas, dissolved hydrocarbons (i.e., short-chain alkanes, BTEX) may serve as exogenous nutrients and could be key factor shaping the composition of the communities. The literature on the topic is full of examples of the capacity of deltaproteobacteria and Firmicutes to grow on these organic molecules (Meckenstock et al, 2016;Lueders, 2017). Microbial communities populating subsurface environments have demonstrated such capacity for the biodegradation of hydrocarbons in the laboratory and in situ.…”
Section: Diversity Of Sulfate-reducing and Methanogenic Metacommunitiesmentioning
confidence: 99%
“…The electron acceptors were consumed in a certain order, with O 2 consumed first, followed by NO reduction, and methane production, respectively [16]. Samples MW3 and MW17 were associated with high Fe 2+ and low SO 4 2− , which indicated that the electron acceptors Fe 3+ and SO 4 2− had been consumed, these two samples probably were in the methanogenesis stage.…”
Section: The Influence Of Electron Acceptors On Bacterial Communitiesmentioning
confidence: 93%
“…Ai-xia Zhou researched the responses of microbial communities to seasonal fluctuations in groundwater level and found that groundwater-table fluctuations would affect the distribution, transport, and biodegradation of the contaminants [15]. Petroleum compounds can be transported from the source area in groundwater, with the result that the petroleum concentrations, redox conditions, biogeochemical processes, and bacterial communities would vary along the groundwater flow path [16]. This view can be supported by other related research, such as from Karolin Tischer, Etienne Yergeau and C.E.…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of microorganisms (bacteria and archaea) have been identified with the capability to degrade hydrocarbon molecules anaerobically. These bacteria exploit anaerobic respiration via nitrate, nitrite, and metal ions or fermentation during substrate catabolism (Lueders, 2017;Portugal et al, 2017).…”
Section: Anaerobic Biodegradationmentioning
confidence: 99%
“…Likewise, this kind of biodegradation can happen beneath the surface of areas where aerobic biological activity has been ceased as all the oxygen is used. After oxygen exhaustion, there may be a consecutive employment of the electron acceptors (nitrate, ferric iron, sulphate, and hydrogen) to supply energy from the hydrocarbon mineralization (Aktas et al, 2017;Arulazhagan et al, 2017;Ghattas et al, 2017;Lueders, 2017).…”
Section: Anaerobic Biodegradationmentioning
confidence: 99%